Role of the Noctiluca scintillans population in the trophic dynamics of the Black Sea plankton over the spring period - Nikishina, A. B.; Drits, A. V.; Vasilyeva, Yu. V.; Timonin, A. G.; Solovyev, K. A.; Ratkova, T. N.; Sergeeva, V. M. (Oceanology (Washington. 1965), 2011)
Noctiluca scintillans is a common and numerous component of the heterotrophic plankton living in the Black Sea. It can play a significant role in the trophic dynamics of the pelagial community. The ingestion rate for the Black Sea Noctiluca is experimentally measured in this article, and its influence on the plankton community over the spring period is estimated. The average grazing of phytoplankton by the N. scintillans population made up about 0.8% in March. In local swarms, it was up to 11%. Noctiluca grazed 4.6% of the primary production per day in June. The grazing of Calanus euxinus eggs by the Noctiluca population varied from 1% to 42% in March. Then, it was 16% in April and 23% in June. The grazing of Acartia clausi eggs was from 1% to 7% in March–April (up to 80% in Noctiluca swarms), from 60% to 817% in May, and 45% in June. The grazing of Calanus faecal pellets was less than 1% in March–April and more than 20% in the beginning of June. It is the first time when the cumulative daily ration (subject to its various food components) for N. scintillans has been measured. The size of the ration was significantly higher than the energy expenditures on metabolism both in March (0.21 μg of C/ind/day) and in the beginning of June (0.28 μg of C/ind/day). Thus, the rapid growth of the population was enabled.